UAV monitoring of excavation works - Shults, Roman; Kassymkanova, Khaini-Kamal; Skopinova, Daria; Demianenko, Roman; Medvedskyi, Yurii (International Conference “Environmental Engineering”, 2020)
The first stage of any construction is carrying out excavation works. These works are high-priced and timeconsuming. Mostly, for geodetic control of the works, the surveyors are using total stations and GNSS equipment. Last decade, UAV technology was a breakthrough in the geodetic technologies market. One of the possible applications of UAV is the monitoring of excavation works. In the article, the opportunities and accuracy of UAV data while performing the excavation works were studied. The surveying of earth volume in the middle of construction works was made using DJI Phantom 4 UAV. The data were being processed using two photogrammetric software: Agisoft Metashape and PhotoModeler Premium. For comparison, the surveying also was made using a conventional total station. For each data source, the 3D models were generated. The obtained models were compared with each other in CloudCompare software. The comparison revealed the high accuracy of UAV data that satisfies customer’s requirements. For the case of two software comparing, it is better to process data using PhotoModeler. The PhotoModeler software allows performing in-depth data analysis and blunders searching.
Keywords: unmanned aerial vehicles; geospatial monitoring; 3D modeling; excavation works; volumes